Comparison of intensity-modulated proton therapy (IMPT) versus intensity-modulated radiation therapy (IMRT) for the treatment of head and neck cancer based on radiobiological modelling. (13th March 2023) - Nguyen, My-Lien; Afrin, Kazi T.; Newbury, Patrick; Henson, Christina; Ahmad, Salahuddin
Abstract: Aim: The aim of our study is to retrospectively report the radiobiological aspects for intensity-modulated proton therapy (IMPT) against intensity-modulated radiation therapy (IMRT) for patients with head and neck cancer treated at our institution. A secondary goal is to reinforce current model-based approaches to head and neck cancer patient selection for IMPT. Materials and Methods: Eighteen patients were evaluated with prescription doses ranging from 50 to 70 Gy delivered in 2 Gy per fraction. The dose volume histograms (DVH) were used to calculate equivalent uniform dose (EUD), tumour control probability (TCP) and normal tissue complication probability (NTCP) for biophysical comparison using mechanistic mathematical dose response models. Absolute values of TCP and NTCP were then compared between IMPT and IMRT. Results: The dose models demonstrate a minimal radiobiological advantage for IMPT compared to IMRT in treating head and neck cancers. Absolute values of TCP were slightly higher, while absolute values of NTCP were slightly lower for IMPT versus IMRT. Conclusions: Further studies are needed to determine if the radiobiological advantage indeed translates to a therapeutic advantage for patients.